Metallic nanoparticles as synthetic building blocks for cancer diagnostics: from materials design to molecular imaging applications1. Issue 28 (28th July 2015) - Mirabello, Vincenzo; Calatayud, David G.; Arrowsmith, Rory L.; Ge, Haobo; Pascu, Sofia I.
<x xml:space="preserve">Abstract</x> New perspectives on the efficiency of metallic nanoparticles as synthetic scaffolds for molecular imaging probe design and their use in medical diagnosis of degenerative diseases such as cancer.